Mothers' satisfaction with care during facility-based childbirth: a cross-sectional survey in southern Mozambique - Sibone Mocumbi; Ulf Högberg; Erik Lampa; Charfudin Sacoor; Anifa Valá; Anna Bergström; Peter von Dadelszen; Khátia Munguambe; Claudia Hanson; Esperança Sevene; the CLIP working group (BMC, 2019)
Abstract Background Client satisfaction is an essential component of quality of care. Health system factors, processes of care as well as mothers' characteristics influence the extent to which care meets the expectations of mothers and families. In our study, we specifically aimed to address the mothers' experiences of, and satisfaction with, care during childbirth. Methods A population-based cross-sectional study, using structured interviews with published sequences of questions assessing satisfaction, including 4358 mothers who gave birth during the 12 months before June 2016 to estimate satisfaction with childbirth care. Regression analysis was used to determine the predictors of client satisfaction. Results Most mothers (92.5%) reported being satisfied with care during childbirth and would recommend that a family member to deliver at the same facility. Specifically, 94.7% were satisfied with the cleanliness of the facility, 92.0% reported being satisfied with the interaction with the healthcare providers, but only 49.8% felt satisfied with the assistance to feed their baby. Mothers who had negative experiences during the process of care, such as being abandoned when needing help, disrespect, humiliation, or physical abuse, reported low levels of satisfaction when compared to those who had not had such experiences (68.5% vs 93.5%). Additionally, they reported higher levels of dissatisfaction (20.1% vs 2.1%). Regression analysis revealed that mothers who gave birth in primary level facilities tended to be more satisfied than those who gave birth in hospitals, and having a companion increased, on average, the overall satisfaction score, with 0.06 in type II health centres (CI 0.03-0.10) and with 0.05 in type I health centres (CI − 0.02 - 0.13), compared to − 0.01(CI -0.08 - 0.07) in the hospitals, irrespective of age, education and socio-economic background. Conclusion Childbirth at the primary level facilities contributes to the level of satisfaction. The provision of childbirth care should consider women's preferences and needs, including having a companion of choice. We highlight the challenge in balancing safety of care versus satisfaction with care and in developing policies on the optimum configuration of childbirth care. Interventions to improve the interaction with providers and the provision of respectful care are recommended.